Comparative Usability Analysis of University Department Websites: A Case Study of Industrial and Chemical Engineering Programs - Kirana, Intania Widyantari; Nugraha, Isna; Novasani, Raditya Jarwenda (Techno.Com, 2025)
This study's goal was to compare the usability of the websites for the Industrial Engineering and Chemical Engineering departments at a university. Since these sites are critical for new students seeking information, a user-friendly interface is essential for efficient and accurate information retrieval. To conduct the study, a user performance test was administered to 40 new students, all with less than a year of study. They were asked to complete three specific tasks: downloading a form, finding a "kaleidoscope" (a summary of activities), and locating information about oral exam registration. The researchers collected data on the time students took to complete the tasks (efficiency) and the number of errors they made. This data was t hen analyzed using a Two-Way ANOVA statistical method. The results showed significant differences in usability between the two websites, with a very strong interaction effect for both efficiency and error rates. The Industrial Engineering website was most efficient for downloading a form but proved to be the least efficient for finding the kaleidoscope. Conversely, the Chemical Engineering website was most efficient for finding the kaleidoscope but was the least efficient for form downloads. Regarding errors, finding the kaleidoscope and downloading a form presented the most significant challenges, while registering for the oral exam was the least error-prone task. These findings highlight the importance of making specific, tailored improvements to academic web design to enhance the user experience on these platforms.   Keywords – Usability; University Website; User Experience; Efficiency; Error Rates